Fibre and Water, The mega nutrients of metabolic health - Kalra , Sanjay; Arora, Saurabh; Kapoor, Nitin (Journal of the Pakistan Medical Association, 2023)
Nutrients are conventionally classified as macronutrients (carbohydrates, fat and protein), and micronutrients (vitamins, minerals, electrolytes). This classification is based upon the quantity required to maintain health, and also, perhaps, the caloric value of the concerned nutrient. We support the use of the descriptor meganutrient for fibre and water. The latter is required in significantly larger quantities to maintain health, and manage metabolic disease such as diabetes and obesity. Fibre has a chemical mega-structure, and its description as a meganutrient reinforces its functions, which are different from other carbohydrates. Keywords: Diet, fibre, H2O, medical nutrition therapy, nutrition, water